(untitled) (KULT_online, 2025)
The edited volume Trauma and Nostalgia: Practices in Memory and Identity explores the relations between trauma, nostalgia, and memory construction across diverse cultural and historical contexts. Drawing on interdisciplinary perspectives, it examines how nostalgia shapes collective identities and influences contemporary perceptions. Case studies, encompassing various localities in Spain, Italy, the US, and Afghanistan, provide valuable insights. As a great practical contribution to memory studies, the book enriches the field with new case studies.